Placental Teratoma Presenting as a Lobulated Mass behind the Neck of Fetus: A Case Report - Adiga Prashanth; Rai Lavanya; K. M. Girisha; Anjali Mundkur (Case Reports in Obstetrics and Gynecology)
Placental teratoma is a rare nontrophoblastic benign tumour, which is thought to arise from germ cells. These tumours contain elements derived from multiple germ cell layers. We report a case of teratoma, where on ultrasound; there were two echogenic masses of 4 cm × 5 cm and 3 cm × 4 cm, arising from the placenta. Elective lower segment cesarean section was done in view of breech presentation at 38 weeks of gestation. Gross examination of the placenta showed two lobulated masses of 5 cm × 5 cm and 4 cm × 4.5 cm, respectively. Histopathological examination of the placenta was suggestive of teratoma of the placenta. The fetus was normal.The maternal and fetal outcome was good.